2022
DOI: 10.1097/ppo.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of FGFR Signaling in Head and Neck Cancer

Abstract: Squamous cell carcinoma of the head and neck (HNSCC) is the sixth most prevalent cancer worldwide, with an annual incidence of 600,000 new cases. Despite advances in surgery, chemotherapy, and radiotherapy, the overall survival for HNSCC patients has not been significantly improved over the past several decades. Fibroblast growth factor (FGF)/fibroblast growth factor receptor (FGFR) genomic alterations are frequently detected in HNSCC, including amplification, activating mutation, and chromosomal rearrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…According to The Cancer Genome Atlas (TCGA) data [ 6 ], amplifications and mutation of FGFR1 , FGFR2 , and FGFR3 are reported to occur in 10%, 2%, and 2% of patients with human papillomavirus–negative cancers, respectively. Other studies have reported FGFR genomic alterations, most frequently focal amplifications in FGFR1 and FGFR3 mutations, in approximately 8.9%-37.3% of HNSCC [ 4 , 7 , 8 ]. Because they are one of the most prevalent receptor tyrosine kinase mutations in HNSCC, the FGFR pathway may serve as a potential, promising therapeutic target [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to The Cancer Genome Atlas (TCGA) data [ 6 ], amplifications and mutation of FGFR1 , FGFR2 , and FGFR3 are reported to occur in 10%, 2%, and 2% of patients with human papillomavirus–negative cancers, respectively. Other studies have reported FGFR genomic alterations, most frequently focal amplifications in FGFR1 and FGFR3 mutations, in approximately 8.9%-37.3% of HNSCC [ 4 , 7 , 8 ]. Because they are one of the most prevalent receptor tyrosine kinase mutations in HNSCC, the FGFR pathway may serve as a potential, promising therapeutic target [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Binding of FGFs to D2-D3 domains initiates FGFR1 dimerization and conformational changes within the intracellular portion of the receptor, resulting in the activation of TK and subsequent FGFR1 autophosphorylation [ 9 , 10 ]. FGFR1 signaling, by controlling fundamental cellular processes like apoptosis, differentiation, division and motility, is critical for the human life at all its stages and its dysregulation is observed in numerous tumors including lung, breast, head and neck and urothelial cancers [ 10 17 ]. Several regulatory mechanisms are engaged in balancing FGFR1 signals such as endocytosis, phosphatases, negative regulatory proteins and feedback signaling [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 In the head and neck, FGFR pathway alterations are frequently detected in squamous cell carcinomas (SCC), most commonly in the forms of FGFR1 amplification (5-30%), FGF amplification (20-25%) and FGFR3 activating mutations (5.8-62%). 2 Oncogenic FGFR rearrangements are rare and mainly represented by FGFR3::TACC3 fusions in approximately 3% of SCC. In addition, FGFR1::PLAG1 fusions were detected in pleomorphic adenoma (PA) and carcinomas ex PA, [2][3][4][5][6] being particularly enriched in myoepithelial carcinomas ex PA. 4,7 However, these tumours are generally considered PLAG1-instead of FGFR1-driven, given that the latter's kinase domain is typically absent in the fusion transcript.…”
Section: Introductionmentioning
confidence: 99%
“…2 Oncogenic FGFR rearrangements are rare and mainly represented by FGFR3::TACC3 fusions in approximately 3% of SCC. In addition, FGFR1::PLAG1 fusions were detected in pleomorphic adenoma (PA) and carcinomas ex PA, [2][3][4][5][6] being particularly enriched in myoepithelial carcinomas ex PA. 4,7 However, these tumours are generally considered PLAG1-instead of FGFR1-driven, given that the latter's kinase domain is typically absent in the fusion transcript. 4 Interestingly, several reports of SCC have concurrently harboured human papillomavirus (HPV) and FGFR3::TACC3 fusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation